(untitled) (Journal of Bangladesh Academy of Sciences, 2021)
Child dietary diversity (CDD) is an important nutritional outcome measuring the economic ability of a household to access a variety of foods during a determined period. Relating household income to CDD and child anthropometric failure, a cross-sectional study was conducted among 275 selected Dhaka city slum children of 6-12 years. Prevalence of stunting (18%), wasting (19.4%), and underweight (22%) among them were found similar to the current national figure. However, a sizable number of households showed increased DDS (>5), thereby indicating an increased household purchasing power (PP). Bivariate regression analysis showed that children from lower family income (≤6000 BDT) were 3 times more likely to be stunted as compared to children with greater family income [Unadjusted OR=3.097, 95% CI (1.578-6.077), p=0.001]. Furthermore, logistic regression showed that children who had <5 DDS were 2 times more likely to be stunted than children who had ≥5 DDS [Adjusted OR=2.127, 95% CI (1.051- 4.305), p=0.036]. Therefore, an inverse association has been found between CDD and their anthropometric failure. J. Bangladesh Acad. Sci. 45(1); 85-94: June 2021